Rapid Characterization and Action Mechanism of the Antidiabetic Effect of Diospyros lotus L Using UHPLC-Q-Exactive Orbitrap MS and Network Pharmacology - Shihan Qin; Mingjuan Liu; Sunv Tang; E. Shuai; Ziming Wang; Kaiquan Yu; Wei Cai (Journal of Analytical Methods in Chemistry)
Diospyros lotus L, F. Ebenaceae, is an edible fruit that is widely distributed in China and other Asian countries. Presently, Diospyros lotus L can be used to treat patients with diabetes; however, its chemical composition and pharmacological profiles remain to be elucidated. This study investigated the potential bioactive compounds of Diospyros lotus L and their mechanisms of action using LC-MS and network pharmacology analysis. First, the components of Diospyros lotus L were identify using a reliable strategy for UHPLC-Q-Exactive Orbitrap mass spectrometry combined with parallel reaction monitoring (PRM) in the negative ion mode. Second, a network pharmacology study, including target gene prediction and functional enrichment, was applied to screen the main quality markers of Diospyros lotus L and explore its potential mechanism for the treatment of diabetes. The results showed that a total of 159 compounds were identified from Diospyros lotus L, among which, 140 were reported for the first time. Furthermore, 40 active components, such as quercetin, luteolin, and kaempferol, were proposed as active components of Diospyros lotus L for the treatment of diabetes based on network pharmacology analysis. In addition, 92 relevant antidiabetic targets were mainly related to positive regulation of transcription from the RNA polymerase II promoter, extracellular space, and protein binding, suggesting the involvement of TNF, PI3K-Akt, and HIF-1 signaling pathways in the antidiabetic effect of Diospyros lotus L. Our results may provide a useful approach to identify potential active components and molecular mechanisms of Diospyros lotus L for the treatment of diabetes.